Resource-based View of Strategic Alliance Formation: Strategic and Social Effects in Entrepreneurial Firms - Eisenhardt, Kathleen M.; Schoonhoven, Claudia Bird (Organization Science, 1996)
Why do firms form strategic alliances? The traditional theoretical answer has been transaction cost explanations. Yet, these explanations which center on transaction characteristics, static efficiency, and routine situations do not capture the strategic and social factors which propel many firms into alliance formation. In this study, however, we combine these alternative social and strategic explanations for alliance formation. Consistent with these explanations, we find that alliances form when firms are in vulnerable strategic positions either because they are competing in emergent or highly competitive industries or because they are attempting pioneering technical strategies. We also find that alliances form when firms are in strong social positions such that they are led by large, experienced, and well-connected top management teams. The underlying logic of alliance formation is, thus, strategic needs and social opportunities. We develop these findings by extending the resource-based view of the firm to alliance formation and then examining the resulting hypotheses using product development alliances. The study is longitudinal and focuses on entrepreneurial semiconductor firms. Overall, strategic and social explanations of organizational phenomena as well as industry, firm, and top management team factors emerge as central in the paper. This suggests that these factors are relevant for predicting alliance formation, especially in high-velocity industries such as semiconductors. We conclude that failure to include social and strategic explanations creates an impoverished view of alliance formation.